2019
DOI: 10.7150/jca.26637
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Prognosis Value of Cumulative Prognostic Scores Based on Serum High-Density Lipoprotein Cholesterol and Albumin Levels in Patients with Colorectal Cancer

Abstract: Aims: Noninvasive tools for the prognosis of colorectal cancer (CRC) are in urgent need. Lipids and proteins have been studied in CRC several years, thus a prognostic indicator based on preoperative serum high-density lipoprotein cholesterol (HDL-C) and serum albumin (ALB) levels (HA score) in CRC patients and to compare the correlation with survival to that of the Glasgow prognostic score.Patient and methods: In the present study, the patient characteristics, clinicopathological factors, and the level of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Hypocholesterolemia has been reported to correlate with worse outcomes and prognosis in a variety of tumors, such as renal cell carcinoma (RCC), CRC, breast cancer, etc. [51][52][53]. Low levels of cholesterol can influence cell membrane fluidity, inhibiting the mobility of cell surface receptors and finally interfering their ability for transmembrane signals transmission [54].…”
Section: Discussionmentioning
confidence: 99%
“…Hypocholesterolemia has been reported to correlate with worse outcomes and prognosis in a variety of tumors, such as renal cell carcinoma (RCC), CRC, breast cancer, etc. [51][52][53]. Low levels of cholesterol can influence cell membrane fluidity, inhibiting the mobility of cell surface receptors and finally interfering their ability for transmembrane signals transmission [54].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that increased systemic inflammatory response and a low nutritional status play important roles in the tumor progression and metastasis, which influence treatment outcomes, prognosis, and survival [12,13]. In recent years, the role of inflammation or nutrition-related factors, including NLR, PLR, albumin levels, and sarcopenia, in malignant tumors have attracted increased attention as significant predictors for various cancers that can reflect tumor' progression [7,8,[14][15][16]. In the current study, high SII and low PNI were correlated with old age, larger tumor size, LVI, pathologic T stage, N stage, and other clinical parameters indicative of an aggressive phenotype, which were consistent with the findings of a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative malnutritional status is also closely related to postoperative survival outcomes in cancer patients 12 . Recently, several studies reported the potential role of novel indicators based on inflammatory and nutritional variables in patients with cancer 13 - 15 . The prognostic nutritional index (PNI), which is calculated from serum albumin level and lymphocyte counts, is one parameters that reflects preoperative nutritional status and has also been validated as an effective prognostic factor in various cancers, including UTUC 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in the Irish Longitudinal Study on Ageing (TILDA), HDL-C was a unique lipid parameter that was not related to the poor prognosis of patients with CRC after two years of follow-up [ 32 ]. In line with the expanding knowledge on the role of HDL in CRC, Huang et al [ 33 ] recently developed a simple prognostic score based on the HDL-C and albumin ratio (HA score). The authors demonstrated a shorter OS and DFS in CRC patients with a high HA score, representing reduced HDL-C and albumin levels [ 33 ].…”
Section: Hdl-c Levels and Hdl Subclass Distribution In Crcmentioning
confidence: 99%